1994
DOI: 10.1136/ard.53.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and vertebral compression fracture rates in ankylosing spondylitis.

Abstract: Objective-To examine the relationship between disease severity and bone density as weli as vertebral fracture risk in patients with ankylosing spondylitis (AS). Methods-Measurements were taken for bone mineral density (BMD) and vertebral fracture rates in 87 patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
7
15

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(149 citation statements)
references
References 10 publications
8
119
7
15
Order By: Relevance
“…On the other hand, comparativelly good spine BMD results are probably "misleading". We as other researchers (Donnelly, 1994;Reid, 1986) support the statement that in the course of the disease, impairment of the spine begins in the form of calcification of longitudinal ligaments and intervertebral discs, formation of syndesmophytes and joint ankylosis. Apparently the decrease in spine mobility caused by changes in the spine may be associated with proximal femoral BMD changes.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, comparativelly good spine BMD results are probably "misleading". We as other researchers (Donnelly, 1994;Reid, 1986) support the statement that in the course of the disease, impairment of the spine begins in the form of calcification of longitudinal ligaments and intervertebral discs, formation of syndesmophytes and joint ankylosis. Apparently the decrease in spine mobility caused by changes in the spine may be associated with proximal femoral BMD changes.…”
Section: Discussionmentioning
confidence: 75%
“…The results revealed that lenghthening disease duration calculated from manifestation of the symptoms is related to vertebral BMD growth and femoral BMD reduction. Agreeing with other authors (Donnelly, 1994;Reid, 1986;Mullaji, 1994), we think that vertebral BMD readings of patients with long disease duration measured by anteriorposterior view of DXA method are merely "deceptive". The lumbar spine often shows misleading high BMD values due to bridging syndesmophytes and ankylosis, which might mask osteoporosis in AS patients with an advanced disease (Donnelly, 1994;Karberg, 2005;Mullaji, 1994;Muntean, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Ankilozan spondilit (AS) genel olarak sakroiliak eklemleri, vertebra ve intervertebral diski etkileyen, sidezmofit oluşumuna ve omurgada hareket kısıtlılığına yol açan kronik inflamatuvar romatizmal bir hastalıktır (1,2). AS'de ve diğer artritlerde yaygın olarak görülen, kemik mineral bozukluklarında etkili olan, inflamatuvar süreç, azalmış mobilite ve/veya değişen hormonal durum gibi çeşitli faktörlerin rolü hala tartışmalıdır (3).…”
Section: Introductionunclassified
“…31 Notably, certain things must be considered when assessing osteoporosis in a patient with syndesmophytes. Donnelley and colleagues 16 revealed that syndesmophytes cause overestimation of bone mineral density on DEXA scans in patients with advanced AS. The increased mineral concentration in the syndesmophyte leads to erroneous assessment of spinal osteoporosis.…”
Section: Osteoporosis In Asmentioning
confidence: 99%
“…Patients with early AS and mild osteoporosis have a fracture prevalence rate 5 times greater than that in the normal population. 16 Other factors that contribute to the increased rates of vertebral fractures include male sex, longer disease duration, and decreased mobility. At this point, it has not been established if these clinical consequences can be prevented with bisphosphonates.…”
Section: Osteoporosis In Asmentioning
confidence: 99%